Case Report: Myxedema Coma Caused by Immunoglobulin A Vasculitis in a Patient With Severe Hypothyroidism - Ito, Hiroshi; Fukuda, Kenzo; Ashida, Kenji; Nagayama, Ayako; Sako, Tomoki; Mizuochi, Kouichiro; Kabashima, Masaharu; Yoshinobu, Satoko; Iwata, Shimpei; Hasuzawa, Nao; Hayashi, Sumika; Akashi, Tomoyuki; et al. (Frontiers in Immunology, 2022)
Myxedema coma is a critical disorder with high mortality rates. Disruption of the compensatory mechanism for severe and long-term hypothyroidism by various causes leads to critical conditions, including hypothermia, respiratory failure, circulatory failure, and central nervous system dysfunction. Infectious diseases, stroke, myocardial infarction, sedative drugs, and cold exposure are considered the main triggers for myxedema coma. A 59-year-old Japanese woman presented with bilateral painful purpura on her lower legs. She was diagnosed with coexisting immunoglobulin A (IgA) vasculitis and severe IgA vasculitis with nephritis and was consequently treated with intravenous methylprednisolone (125 mg/day). However, she rapidly developed multiple organ failure due to the exacerbation of severe hypothyroidism, i.e., myxedema. Her condition improved significantly following oral administration of prednisolone along with thyroxine. There was a delayed increase in the serum free triiodothyronine level, while the serum free thyroxine level was quickly restored to normal. Rapid deterioration of the patient’s condition after admission led us to diagnose her as having myxedema coma triggered by IgA vasculitis. Hence, clinicians should be aware of the risks of dynamic exacerbations in patients with hypothyroidism. Furthermore, our study suggested that combination therapy with thyroxine and liothyronine might prove effective for patients with myxedema coma, especially for those who require high-dose glucocorticoid administration.